Technical and Diagnostic Issues in Whole Slide Imaging Published Validation Studies - Rizzo, Paola Chiara; Girolami, Ilaria; Marletta, Stefano; Pantanowitz, Liron; Antonini, Pietro; Brunelli, Matteo; Santonicco, Nicola; Vacca, Paola; Tumino, Nicola; Moretta, Lorenzo; Parwani, Anil; Satturwar, Swati; et al. (Frontiers in Oncology, 2022)
Objective. Digital pathology with whole-slide imaging (WSI) has shown many potential clinical and non-clinical applications. In the past decade, despite significant advances in WSI technology adoption remains slow for primary diagnosis. The aim of this study was to identify common pitfalls of WSI validation studies and assess potential measures to overcome these challenges. Methods. A systematic search was carried out in electronic databases Pubmed-MEDLINE and Embase. Inclusion criteria were all validation studies designed to evaluate the feasibility of WSI for diagnostic clinical use. Technical and diagnostic problems encountered with the use of WSI during these studies were recorded. Results. Forty-five works were included reporting technical issues in 15 studies (33%), diagnostic issues in 8 papers (18%), and both kinds of problems in 22 (49%). Key technical topics were related to scanning failures, prolonged turn-around times, and need for higher magnification. Diagnostic challenges were concerned with grading dysplasia, assessment of mitotic count, identification of microorganisms, and defining the invasive front of tumors. Conclusions. Improvements have occurred with WSI technology, but some critical issues remain. More focus on the quality of pre-scanning phase handling and training of pathologists could help reduce the impact of WSI technical difficulties. Critical issues regarding specific diagnostic tasks also remain a challenge, which likely represent suboptimal reproducibility among pathologists also seen when examining glass slides with conventional light microscopy.